PTH-082 Do Serum Markers Of Cell Injury And Death Have Potential To Become Mechanistic Markers In Non-alcoholic Fatty Liver Disease (nafld)?. (9th June 2014) - Grove, JI; Antoine, DJ; Kaye, P; Miller, MH; Dillon, JF; Allison, ME; James, MW; Wilkes, EA; Jackson, AP; Guha, IN; Williams, DP; Aithal, GP
Abstract : Introduction: Degree of hepatocellular injury, necrosis/apoptosis and inflammation may be assessed by the serum markers that reflect the pathogenic process. We investigated the correlation of circulating miR-122, High Mobility Group Box-1 (HMGB1), soluble Fas (sFas) and caspase-cleaved fragment of keratin-18 (CK18) with histological changes in liver biopsy of patients with non-alcoholic fatty liver disease (NAFLD). Methods: Serum analytes were determined in two independent cohorts of patients with NAFLD (derivation cohort n = 165, validation cohort n = 101). Histological parameters were scored using Clinical Research Network system; patients with NAFLD activity scores (NAS) of ≥3 were classified as borderline non-alcoholic steatohepatitis (NASH) and ≥ 5 as definite NASH. Results: There were no significant differences in miR-122, HMGB1, sFas and CK18 M30 levels between those with low (0–2) and high (3–4) stage of fibrosis. Both CK18 M30 as well as CK18 M65 correlated with grades of ballooning (p = 0.003 and p = 0.001) and lobular inflammation (p = 0.006 and p = 0.001). Table 1 summarises the serum levels of all the evaluated markers in subgroups of patients classified as borderline or definite NASH when only patients with low grade fibrosis were included (derivation cohort, n = 145 and validation cohort, n = 90). Importantly, when the cut-off values for CK18 M30 (395 U/L) was used on its own, 57/86 (66%) patients with definite NASH were missed. Conclusion: Biomarkers, UKof cell injury and death in combination have a potential to detect on-going histological activity in NAFLD. Disclosure of Interest: None Declared.